"To each his own": Discussions of vaccine decision-making in top parenting blogs. Issue 8 (3rd August 2017) - Meleo-Erwin, Zoë; Basch, Corey; MacLean, Sarah A.; Scheibner, Courtney; Cadorett, Valerie
ABSTRACT: Although social media provides a way for people to congregate with like-minded others, it can also play a role in spreading misinformation about public health interventions. Previous research demonstrates that parents who use the Internet to gather information on vaccination are more likely to hold anti-vaccination beliefs. There has been little examination of vaccination decision-making discussions on parenting blogs. This study seeks to fill that gap. Posts and comments on the top 25 top parenting blogs were analyzed using a mixed-method approach. Comments were analyzed using deductive coding scheme that examined whether content areas of interest were present or absent in vaccination discussions. Posts were coded inductively using a thematic analysis. Posts and comments were further coded as strongly vaccine-discouraging, vaccine-ambivalent, or strongly vaccine-encouraging. Finally, posts were grouped by year of publication and comments were analyzed within each group to examine the evolution of vaccination decision-making discussions in the parenting blogosphere over the past decade. Fifty-two percent of posts were categorized as strongly vaccine-discouraging and were most commonly associated with expressions of individual liberty. Comments were nearly 3 times as likely to strongly discourage vaccination than to strongly encourage it. Comments on the oldest posts (2006–2009), were more likely to strongly discourage vaccination (p = 0.008), whereas comments on newer posts (2013–2015), were more likely to strongly encourage vaccination (p = 0.003). These findings suggest there is a need for public health professionals to understand the concerns being expressed in these forums, and develop innovative ways to dispel anti-vaccination myths, as these views may create obstacles in the meeting the goals of the public health agenda.